Greenwashing or Genuine Governance? A Review of ESG Strategies in Mitigating Earnings Management - Wahyuni, Putri Dwi (CV. Rayyan Dwi Bharata, 2025)
This study conducts a comprehensive review of the relationship between Environmental, Social, and Governance (ESG) practices and profit management behavior in companies, with a specific focus on identifying genuine practices versus greenwashing. Using a systematic literature review method on 54 research articles published in reputable Scopus journals, the results of this study reveal three main findings: First, substantive ESG implementation significantly reduces accrual-based earnings management through increased transparency and strengthened corporate governance structures. Second, empirical evidence suggests that some companies use ESG disclosure as a greenwashing strategy to conceal earnings manipulation activities, particularly through real activities manipulation. Third, the effectiveness of ESG in mitigating earnings management is significantly influenced by contingency factors such as regulatory strength, industry characteristics, and corporate ownership structure. These findings have important implications for regulators in developing stricter ESG oversight frameworks and for investors in developing more comprehensive criteria for evaluating sustainable investments.